Non-stoichiometric fibrous apatite for heavy metal ion capture - Tan, Amos Zhong Min. (2009)
In this study, two different methods were used to synthesis hydroxyapatite (HA, Ca10(PO4)6(OH)2). Fibrous HA was synthesised by hydrothermal reaction and HA powders were obtained from high temperature solid state reaction. Kinetics and thermodynamics of lead sorption from aqueous lead nitrate solutions with initial lead concentration of 2590 ppm by fibrous HA and HA powders were investigated for different durations, between 1-336 hours at various temperatures of 23°C, 50°C and 80°C. It was deduced by Rietveld analysis that the sorption capacities of both HA materials increased with the increase in temperature through the growing proportions of hydroxypyromorphite (HP), Pb10(PO4)6(OH)2. Fibrous HA displayed better performance in better lead uptake capabilities due to their higher solubility, lower crystallinity and oriented crystals as compared to HA powders. The maximum sorption capacity of fibrous HA for Pb2+ ions at 80°C for 240h was 2.42 mmol/g relative to 0.67 mmol/g for the HA powders at the same temperature, with 2.50 mmol/g being the maximum possible amount of lead sorbed by HA. Fresh HA materials and samples previously exposed to lead were also analyzed via scanning electron microscopy (SEM) and the detection of HP reinforced the hypothesis that its formation is the end of a kinetic process in which the HP crystals are continuously dissolved and recrystallised in order to form more stable structures with higher lead content. The first-order kinetic model was used to describe the kinetic data, and the data constants were evaluated. The activation energy was also calculated from fitting the Arrhenius equation with the graph of ln K against temperature inverse. Fibrous HA has activation energy of 54.92kg/mol. Hence, fibrous HA can be considered as a potential adsorbent for the remediation of lead ions in contaminated industrial wastewaters.